Implications of the neoliberalism expansion process in the initial teaching formation: an analysis from UNESCO documents - Lucas de Paula Rodrigues; Vânia de Fátima Matias de Souza (Universidade Federal do Norte do Tocantins, 2022)
The aim of the present study was to investigate the implications of the expansion of neoliberalism in the reform of the state apparatus and its relationship with the Initial Teacher education. It was supported by bibliographic research with documentary analysis. For the lessons in the field of initial teacher training, Dakar and Incheon conferences were rescued. The analyzes indicate that the reform of the state, fostered by international organizations, influences the dynamics of educational institutions and teacher training through the establishment of the pillars of managerial administration in the educational field, given that it is observed in world education conferences, a consensus on teacher training and the assumptions chosen as structural and cyclical objectives for society itself. The implicit indications in these documents show the need for internal and external evaluation processes based on the concepts of efficiency, competitiveness and productivity, establishing a relationship between inspection, control and regulation of the current educational scenario.